Experiences and Attitudes of Nurses Regarding Complementary Health Approaches Used by Themselves and Their Patients. (July 2017) - Cırık, Vildan; Efe, Emine; Öncel, Selma; Gözüm, Sebahat
Nurses' attitudes and experiences may affect the level of patient exposure to complementary health approaches (CHA), both now and in the future. The purpose of this study was to describe nurses' experience of CHA and their personal and professional attitudes to the use of CHA. The sample consisted of 220 nurses working at a university hospital in Antalya, Turkey. Data were collected using a questionnaire developed by the researchers. Nurses had a positive attitude toward CHA and reported mixed experiences of CHA for allergies, pain, and stress. This study may contribute to increased awareness of the potentially important role of nurses in delivery of CHAs. Hospital nurses should receive more training on CHA. Nurses should discuss the potential benefits and risks of CHA with patients.